Corrosion of Mg-9Al alloy with minor alloying elements (Mn, Nd, Ca, Y and Sn). (15th September 2017) - Mingo, B.; Arrabal, R.; Mohedano, M.; Mendis, C.L.; del Olmo, R.; Matykina, E.; Hort, N.; Merino, M.C.; Pardo, A.
Abstract: Microstructure and corrosion behaviour of a Mg-9Al alloy with minor alloying additions (Mn, Y, Nd, Ca and Sn) are evaluated. All of the additions form Al-rich intermetallics with varying amounts of Fe, while Ca and Sn are also incorporated into the eutectic β-phase (β-Mg17 Al12 ). Special attention is given to the surface potential values of the microconstituents, which are related to the formation of microgalvanic couples. Scanning Kelvin Probe Force Microscopy (SKPFM) measurements revealed that all the alloying elements, except Sn, reduced the potential difference between the secondary phases and the matrix, which is the main reason for the improvement of the corrosion resistance of Mn-, Y- and Nd-modified alloys. The beneficial effect of Ca is additionally related to the microstructure refinement and an increased area fraction of the β-phase. Graphical abstract: Highlights: Additions of Mn, Y and Nd to Mg-9Al lead to their incorporation to Al-Fe-rich particles, reducing their surface potential value. Additions of Ca and Sn modify the nature of the β-phase, increasing and decreasing respectively, its surface potential value. All alloying elements improve the corrosion resistance of Mg-9Al alloy, mainly due to the reduced galvanic coupling. Ca positive influence is related to the β-phase refinement and increased area fraction, which boost its barrier effect.